Comprehensive evaluation on effective leaching of critical metals from spent lithium-ion batteries. (May 2018) - Gao, Wenfang; Liu, Chenming; Cao, Hongbin; Zheng, Xiaohong; Lin, Xiao; Wang, Haijuan; Zhang, Yi; Sun, Zhi
Graphical abstract: Highlights: A comprehensive evaluation of spent lithium-ion battery recycling was carried out. The leaching speed and recovery rate were defined to evaluate the leaching process. It is expected to attain the preliminary principle to control the leaching solution. Abstract: Recovery of metals from spent lithium-ion batteries (LIBs) has attracted worldwide attention because of issues from both environmental impacts and resource supply. Leaching, for instance using an acidic solution, is a critical step for effective recovery of metals from spent LIBs. To achieve both high leaching efficiency and selectivity of the targeted metals, improved understanding on the interactive features of the materials and leaching solutions is highly required. However, such understanding is still limited at least caused by the variation on physiochemical properties of different leaching solutions. In this research, a comprehensive investigation and evaluation on the leaching process using acidic solutions to recycle spent LIBs is carried out. Through analyzing two important parameters, i.e. leaching speed and recovery rate of the corresponding metals, the effects of hydrogen ion concentration, acid species and concentration on these two parameters were evaluated. It was found that a leachant with organic acids may leach Co and Li from the cathode scrap and leave Al foil as metallic form with high leaching selectivity, while that with inorganic acids typically leach all metals into the solution. Inconsistency between the leaching selectivity and efficiency during spent LIBs recycling is frequently noticed. In order to achieve an optimal status with both high leaching selectivity and efficiency (especially at high solid-to-liquid ratios), it is important to manipulate the average leaching speed and recovery rate of metals to optimize the leaching conditions. Subsequently, it is found that the leaching speed is significantly dependent on the hydrogen ion concentration and the capability of releasing hydrogen ions of the acidic leachant during leaching. With this research, it is expected to improve understanding on controlling the physiochemical properties of a leaching solution and to potentially design processes for spent LIBs recycling with high industrial viability.